Physical activity behaviour up to 1 year post-rehabilitation among adults with physical disabilities and/or chronic diseases: results of the prospective cohort study ReSpAct - Lucas H V van der Woude; Rienk Dekker; Trynke Hoekstra; Leonie A Krops; Femke Hoekstra; Florentina J Hettinga; Pim Brandenbarg; Bregje L Seves (BMJ Open, 2022)
Background Little is known of physical activity behaviour among adults with a disability and/or chronic disease during and up to 1 year post-rehabilitation. We aimed to explore (1) dose characteristics of physical activity behaviour among adults with physical disabilities and/or chronic diseases during that period, and (2) the effects of personal characteristics and diagnosis on the development of physical activity over time.Methods Adults with physical disabilities and/or chronic diseases (N=1256), enrolled in the Rehabilitation, Sports and Active lifestyle study, were followed with questionnaires: 3–6 weeks before (T0) and 14 (T1), 33 (T2) and 52 (T3) weeks after discharge from rehabilitation. Physical activity was assessed with the adapted version of the Short Questionnaire to ASsess Health enhancing physical activity. Dose characteristics of physical activity were descriptively analysed. Multilevel regression models were performed to assess physical activity over time and the effect of personal and diagnosis characteristics on physical activity over time.Results Median total physical activity ranged from 1545 (IQR: 853–2453) at T0 to 1710 (IQR: 960–2730) at T3 min/week. Household (495–600 min/week) and light-intensity (900–998 min/week) activities accrued the most minutes. Analyses showed a significant increase in total physical activity moderate-intensity to vigorous-intensity physical activity and work/commuting physical activity for all time points (T1–T3) compared with baseline (T0). Diagnosis, age, sex and body mass index had a significant effect on baseline total physical activity.Conclusion Physical activity is highly diverse among adults with physical disabilities and/or chronic diseases. Understanding this diversity in physical activity can help improve physical activity promotion activities.